Questioning Presidential Threshold in Indonesia: Constitutional Analysis and Democracy Implementation - Hakim, Dani Amran; al Arif, M Yasin (Veteran Law Review, 2024)
General elections serve as a democratic mechanism aimed to a lawful transition of power based on the constitution. The legal basis for general elections is found in Article 22E, while the election of the President and Vice President is governed by Article 6A of the 1945 Constitution of the Republic of Indonesia. There is no provision regarding the presidential threshold in the 1945 Constitution, as this regulation is an additional provision in Article 222 of Law Number 7 of 2017 concerning General Elections. The research methodology employs normative legal research with a juridical and conceptual approach by examining and studying relevant literature on the research topic. From a constitutional perspective, the presidential threshold provision lacks constitutional grounds. Constitutionally, every citizen has equal rights before the law and in governance. However, this limitation impacts an individual's right to be elected and to vote. From the democratic principle standpoint, political parties as representatives of the people will be restricted according to the regulations of the presidential threshold. This regulation, based on the previous general election results, eliminates the political rights of new or small parties to nominate candidates for President and Vice President.